Dari Medan Perang Berburu Lapangan Pekerjaan: Pengangguran Revolusi di Yogyakarta Tahun 1950-an - Rika Inggit Asmawati (Universitas Gadjah Mada, 2016)
This research discusses about the social economic history of Yogyakarta during 1950s. The main problem is to analyze how the newly independent country of Indonesia dealt with unemployment after the revolutionary period. This research employs the historical method using primary and secondary sources, such as archives, newspapers, magazines, interviews, and reviews of relevant references. There are four conclusions in this research. First, although the period was called as the period of creating jobs, the unemployment number in early 1950s was increasing. Second, this unemployment problem was not primarily caused by the economic condition but also by demographic problems and the legacies from the Revolution Era. Third, people who were categorized as unemployed were not only labors, but also veterans. Fourth, for the government, solving this unemployment problem was the effort to create economic improvement for its society.